2011
DOI: 10.2478/s11535-011-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonsteroidal ecdysone agonist RH-5992 and chitin biosynthesis inhibitor lufenuron on Spodoptera littoralis (Boisduval, 1833)

Abstract: Abstract:Comparative studies of the effects of two compounds, tebufenozide (an ecdysone agonist) and lufenuron (an insect growth regulator inhibiting chitin synthesis), were conducted on Spodoptera littoralis (Boisduval, 1833). The compounds, orally administered, caused larval mortality proportional to the concentrations in the food source. Tebufenozide initiated precocious molting, and lufenuron, and inhibited chitin synthesis. In both cases, larvae were unable to complete the molting process and died in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
4
9
0
Order By: Relevance
“…These findings could be linked with Wang and Tian (2009) and Gelbic et al (2011) who successfully tested IGRs compounds against several insect species example Spodoptera litura and S. littoralis which inhibits or prevents normal metamorphosis of immature stages to the adult stages.…”
Section: Efficacy Of Buprofezin On Weight Reduction Of Spodoptera Litmentioning
confidence: 75%
See 2 more Smart Citations
“…These findings could be linked with Wang and Tian (2009) and Gelbic et al (2011) who successfully tested IGRs compounds against several insect species example Spodoptera litura and S. littoralis which inhibits or prevents normal metamorphosis of immature stages to the adult stages.…”
Section: Efficacy Of Buprofezin On Weight Reduction Of Spodoptera Litmentioning
confidence: 75%
“…Among different IGRs Buprofezin is one of the important chitin synthesis inhibitors (CSIs) that prevent chitin bio-synthesis and deposition in insect body. As a result, new cuticle formation is arrested and old cuticles become fractured and insect finally die (Gelbic et al, 2011;Mulder, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms exposed to these EcR agonists fail to shed their old exoskeletons during molting (i.e., incomplete ecdysis; event 990) and suffer from increased mortality (event 351) as a result of a combination of physiological abnormalities and reduced feeding. This molting defect-associated AO has been widely reported in insects such as the spruce budworm (Choristoneura fumiferana), cotton leafworm (Spodoptera littoralis), and tobacco hornworm (Manduca sexta) [14,25,28] and occasionally reported in crustaceans such as the water flea (Daphnia magna), crab (Rhithropanopeus harrisii), and barnacle (Balanus amphitrite) [29,30] for both endogenous (e.g., 20E) and exogenous (e.g., TEB) EcR agonists. Individual mortality may potentially affect the population size and ultimately cause population decline.…”
Section: Case Study 1: Ecdysone Receptor Activation Leading To Mortalitymentioning
confidence: 77%
“…Methoxyfenozide is a potent ecdysone agonist against Lepidoptera by ingestion, and this compound is highly active, and to a lesser degree, by contact or topical application. The results indicated that Methoxyfenozide significantly reduced both of the total number of eggs laid and their hatching rate in comparison with the control similarly like tebufenozide (Gelbič et al 2011). This reduction in fecundity is most likely caused by the ecdysone agonists affecting the female reproductive system.…”
Section: Discussionmentioning
confidence: 82%